“COMPLICATED MATHEMATICS DEB ACCOUNTING CONCEPT” PENGGUNAAN DAN PENERAPAN UNTUK KERANGKA PEMBELAJARAN PADA ACCOUNTING SCENTS AND ACCOUNTING PROBLEMS - Husni Mubarak; Rosmida Rosmida (Politeknik Negeri Bengkalis, 2018)
Abstract: This article investigated about mechanism of double entry bookkeeping (DEB) on the usage side of the learning process. Focus assessment of this article is on the develop use of complex accounting equations. Transformation complexcity transaction is about balance sheet, income and equity. Accounting equiation frmawork find universal modification implementation, that only simple equations but complax equaiton this transaction. That simple information, this equestion (A=L+E) is become more complex component A (Cr.A+Fx.A +It.A) = L (Cr.L+LT.L) + E (CS+RE+R). But this consept in article have weakness and limitations, only use argument, assumtion and basic analisys in define framework modification, and need complex understanding and scientific evidence.